Professor János Sugár 1922-2010 - Tompa, Anna (European Journal of Oncology and Environmental Health, 2010)
His interest focused on determination of the preneoplasticprocesses, the reversible and irreversiblephenotypic and more recently the genotypic characterization.He firstly described the electron microscopicmicroinvasion preceding the real invasionoccurring in serious dysplastic tumors in skin, laryngeal,breast and gastroenteric pre-cancerous states(Europ J Cancer, 1968)...